Efecto de Bencil amino purina en el crecimiento de segmentos nodales de Vanilla planifolia Jacks ex Andrews mediante propagación in vitro laboratorio INIBICO Tarapoto Perú - Díaz Salas, Simith del Carmen (2025)
Vanilla planifolia Andrews, known as vanilla, is an orchid, climber that belongs to the Orchidaceae family, currently its demand has increased internationally, by having vanillin, natural flavoring substance of greater importance, used in the food industry, liquor, pharmaceutical, perfumery, cosmetics and medicine (3). There are research works, through in vitro propagation, manipulating different levels of concentration of phytoregulators growth, as an alternative to obtain healthy, strong plants and improve their cultivation that helps improve the availability of plants and their subsequent implantation in the field. The objective was to evaluate the effects of different levels of concentration of cytokinins (BAP), from nodal segments, on the growth of the number and length of shoots, nodes, leaves, roots and stem. Data analysis, ANOVA and Tukey's test were used to observe significant differences. The results showed a slight growth of the nodal segments of the species under study, in the shoots, nodes, leaves, roots and stem, at different BAP concentrations: T1, 0.75 mg / L-1, T2, 1.50 mg / L-1, T3, 3.00 mg / L-1. The Tukey test indicates that there are no significant differences for presenting the same letter (A) and the average of the means does not vary between 1, at the different concentration levels, with the treatments applied for the optimal growth of the variables.